2013
DOI: 10.1371/journal.pone.0068306
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Expression of PTPRJ/CD148 and an Antisense Long Noncoding RNA in Macrophages by Proinflammatory Stimuli

Abstract: PTPRJ/CD148 is a tyrosine phosphatase that has tumour suppressor-like activity. Quantitative PCR of various cells and tissues revealed that it is preferentially expressed in macrophage-enriched tissues. Within lymphoid tissues immunohistochemistry revealed that PTPRJ/CD148 co-localised with F4/80, indicating that macrophages most strongly express the protein. Macrophages express the highest basal level of ptprj, and this is elevated further by treatment with LPS and other Toll-like receptor ligands. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 81 publications
1
29
0
Order By: Relevance
“…35,No. 9 (RNA-Seq) have now demonstrated differential lncRNA expression following activation of monocytes, macrophages, dendritic cells, and fibroblasts, as well as following viral infection in mouse lungs [15,25,26,28,[33][34][35] ( Table 1). As outlined in the following sections, investigators have then examined the role of individual lncRNAs in the innate immune response.…”
Section: Keymentioning
confidence: 99%
“…35,No. 9 (RNA-Seq) have now demonstrated differential lncRNA expression following activation of monocytes, macrophages, dendritic cells, and fibroblasts, as well as following viral infection in mouse lungs [15,25,26,28,[33][34][35] ( Table 1). As outlined in the following sections, investigators have then examined the role of individual lncRNAs in the innate immune response.…”
Section: Keymentioning
confidence: 99%
“…Many identified lncRNAs, including lncRNA-Nfkb2 and lncRNA-Rel, were located near protein-coding regions of immune response genes and contained binding sites for the transcription factors NF-kB (p65), IRF3, Jun-B, or c-Jun [112]. Analyses of LPS-stimulated mouse BMDMs identified the highly up-regulated Ptprj-as1 lncRNA, which is transcribed as AS to Ptprj [114], a type III receptor protein tyrosine phosphatase that regulates monocyte activation by modulating Src kinases [115,116]. Ptprj-as1 is located close to putative transcription factor-binding sites, suggesting that it could play an important role in regulating monocyte activation and responsiveness to LPS.…”
Section: Tlr4 Signalingmentioning
confidence: 99%
“…The relationships between miR‐155 and the above three factors have been widely reported in cancer cells and immune cells [Kutty et al, ; Peyrou et al, ; Wan et al, ]. So the interaction of PTPRJ and miR‐155 might imply an involvement of PTPRJ in immune system; indeed, several reports have demonstrated that PTPRJ functioned in inflammatory responses [Dave et al, ,; Jablonski et al, ]. It is worth exploring the regulatory mechanisms of PTPRJ to NRF/PPAR/STAT3 signaling and investigating the action of miR‐155 in these axes.…”
Section: Discussionmentioning
confidence: 99%